Effects of input vouchers and rainfall insurance on agricultural production and household welfare: Experimental evidence from northern Ethiopia. (November 2020) - Wong, Ho Lun; Wei, Xiangdong; Kahsay, Haftom Bayray; Gebreegziabher, Zenebe; Gardebroek, Cornelis; Osgood, Daniel E.; Diro, Rahel
Highlights: Input vouchers increased usage of seeds and fertilizers, raised farmland size, and induced labor substitution. Subsidized rainfall insurance with reduced input vouchers produced weak effects but greatly increased investments for patient farmers. We do not find heterogeneous effects by farmer's risk aversion levels. Insurance demand did not correlate with time or risk preference, however, and dropped quickly with the reduction in subsidy. Initial subsidies increase future insurance demand, but alone would not be a cost-effective mechanism for financially sustainable insurance. Abstract: We report on a randomized field experiment designed to relax credit and risk constraints for agricultural activities. We conducted a study in a drought-prone region in northern Ethiopia among poor smallholders who depended on rainfed agriculture and were members of the Productive Safety Net Programme (PSNP). Data were collected from over 1100 farmers in 32 rural villages over two years. We find that unconditional voucher transfers designated for the purchase of agricultural inputs significantly increased usage of seeds and fertilizers (a flypaper effect), raised the amount of farmland used (a complementary effect), and induced substitution of own effort by hiring casual labor (a local spillover effect). Subsidized rainfall insurance with reduced input vouchers produced weak average effects but greatly increased investments for farmers who were relatively more patient. We do not find heterogeneous effects by farmers' risk attitudes, however, suggesting that the effects of insurance adoption were mainly determined by how farmers in the safety net made tradeoffs inter-temporally. Insurance demand dropped quickly with the reduction in subsidy and did not correlate with time or risk preference. Therefore, to improve cost-effectiveness, insurance programs should include procedures that help identify forward-looking farmers and encourage their adoption. While our results show that initial subsidies increase future insurance demand, the effect was small and thus initial subsidies would not be a cost-effective mechanism for financially sustainable insurance. Other complementary strategies on the design, promotion, and bundling techniques of insurance would be needed.